Wood substrate type shapes isotopic composition and growth performance in a shipworm (Bivalvia: Teredinidae) - François Charles; Pascal Riera; Benoit Lebreton; Gaël Guillou; Fabien Aubert; Erwan Peru; François Lantoine (Journal of Experimental Marine Biology and Ecology, 2026)

Using stable isotope analysis to determine the effects of ocean acidification and warming on trophic interactions in a maerl bed community - Erwann Legrand; Sophie Martin; Cédric Leroux; Pascal Riera (Marine Ecology, 2020)
Ocean acidification and warming are likely to affect the structure and functioning of marine benthic communities. This study experimentally examined the effects of ocean acidification and warming on trophic interactions within a maerl bed community by using stable carbon and nitrogen isotope analysis. Two three‐month experiments were conducted in winter and summer seasons with four different combinations of pCO 2 (ambient and elevated pCO 2 ) and temperature (ambient and +3°C). Experimental assemblages were created in tanks held in the laboratory and were composed of calcareous ( Lithothamnion corallioides ) and fleshy algae ( Rhodymenia ardissonei , Solieria chordalis, and Ulva sp.), gastropods ( Gibbula magus and Jujubinus exasperatus ), and sea urchins ( Psammechinus miliaris ). Our results showed higher seaweed availability for grazers in summer than winter. Therefore, grazers were able to adapt their diet seasonally. Increased pCO 2 and temperature did not modify the trophic structure in winter, while shifts in the contribution of seaweed were found in summer. Combined acidification and warming increased the contribution of biofilm in gastropods diet in summer conditions. Psammechinus miliaris mostly consumed L. corallioides under ambient conditions, while the alga S. chordalis became the dominant food source under high pCO 2 in summer. Predicted changes in pCO 2 and temperature had complex effects on assemblage trophic structure. Direct effects of acidification and warming on seaweed metabolism may modify their abundance and biomass, affecting their availability for grazers. Climate change may also modify seaweeds' nutritive value and their palatability for grazers. The grazers we investigated were able to change their diet in response to changes in algal assemblages, an advantage given that warming and acidification alter the composition of algal communities.

Effect of temperature on an alga‐grazer trophic transfer: A dual stable isotope ( 13 C, 15 N) labeling experiment - Erwann Legrand; Sophie Martin; Cédric Leroux; Pascal Riera (Marine Ecology, 2018)
In this study, we examined the impact of temperature on the carbon and nitrogen trophic transfers from a macroalga to a macro‐grazer by the use of dual 13 C‐ and 15 N‐labeling. Using an experimental approach in mesocosms, individuals of the urchin Psammechinus miliaris were maintained for 1 month at 17°C (mean summer temperature in the Bay of Brest) and at 20°C (maximum summer temperature) and fed with 13 C‐ and 15 N‐labeled Solieria chordalis. The results showed that the urchins’ 13 C uptake was 0.30 µg 13 C g dry weight (DW) −1 at 17°C and 0.14 µg 13 C g DW −1 at 20°C at the end of the experiment. The lower uptake at the higher temperature may be attributed to a decrease in metabolic activity at 20°C, involving lower feeding and/or respiration rates. Conversely, no significant effect of temperature was detected on 15 N uptake. At the end of the experiment, the urchins’ 15 N uptake was 0.04 µg 15 N g DW −1 at 17°C and 0.03 µg 15 N g DW −1 at 20°C. This suggests that temperature may affect carbon and nitrogen trophic fluxes differently. The use of dual isotope labeling offers interesting prospects and needs to be further extended in order to better understand trophic interactions in marine communities and the consequences of current environmental changes, such as global warming.

Contrasting temporal variation in habitat complexity and species abundance distributions in four kelp forest strata - Jean-Charles Leclerc; Pascal Riera; Laurent Lévêque; Dominique Davoult (Hydrobiologia, 2016)

Biodiversity and trophic structure of invertebrate assemblages associated with understorey red algae in a Laminaria digitata bed - Gauthier Schaal; Jean-Charles Leclerc; Gabin Droual; Cedric Leroux; Pascal Riera (Marine Biology Research, 2016)

How are microbial and detrital sources partitioned among and within gastropods species at E ast P acific R ise hydrothermal vents? - Sylvie M. Gaudron; Lise Marqué; Eric Thiébaut; Pascal Riera; Sébastien Duperron; Magali Zbinden (Marine Ecology, 2015)
For the last few decades, trophic ecology has usually been investigated by using stable isotopes. However, the isotopic signatures of potential food sources in hydrothermal vent ecosystems are often unknown and so their relative contribution to the consumers’ diet, as well as resource partitioning, are then difficult to estimate. Here, we used a recent B ayesian mixing model (stable isotope analysis in R , SIAR ) based on δ 13 C and δ 15 N to estimate the contribution of multiple food sources to the diet of eight vent gastropods that can reach high densities at hydrothermal vents ( L epetodrilus elevatus , L epetodrilus pustulosus , L epetodrilus ovalis , E ulepetopsis vitrea , C yathermia naticoides , P eltospira delicata , P eltospira operculata and R hynchopelta concentrica ). These species, known as primary consumers (mostly bacterivores and detritivores), were sampled on the S outh‐ E ast P acific R ise at 17°25′ S and the N orth‐ E ast P acific R ise at 9°50′ N and 12°50′ N. Several potential food sources were sampled according to the gastropod habitat on the chimney wall, or mussel beds (proxies of G ammaproteobacteria form I R ubis CO , G ammaproteobacteria form II R ubis CO and E psilonproteobacteria , biofilms of siboglinid and alvinellid tubes, biofilms of mussel shells and particulate organic matter). Some of these microbial and detrital sources were confirmed as present in the gut content of some small specimens by transmission electron microscopy. Distinct stable isotopic signatures of the potential food sources allowed calculation of their relative contributions to primary consumers’ diets. This revealed that gastropod species living on siboglinid or bathymodiolin habitats are usually generalists, feeding on various pools of microbial or detrital origins. For a particular habitat, sympatric gastropod species partition the food sources, thus avoiding being in competition. Only for the alvinellid habitat P eltospira spp. appeared to be more specialists as the choice of food sources is more reduced.

Trophic ecology of P omatoschistus microps within an intertidal bay ( R oscoff, F rance), investigated through gut content and stable isotope analyses - Jean‐Charles Leclerc; Pascal Riera; Laure M.‐L. J. Noël; Cédric Leroux; Ann C. Andersen (Marine Ecology, 2014)
The diet of P omatoschistus microps has been studied using both gut content and stable isotope analyses. In the R oscoff A ber B ay ( B rittany, F rance), this fish is commonly found on sandy muddy intertidal flats. Gut content analyses were also interpreted using trophic indices. Owing to the large diversity of prey consumed, these indices emphasised the opportunistic feeding behaviour of P . microps . Here, this species fed mainly on endofauna with meiofauna being of high relative importance. The main biotic components of its trophic habitat, characterized by δ 13 C and δ 15 N , provided evidence of a major trophic pathway based on drift E nteromorpha sp. Trophic positions estimated by both diet analyses and isotopic analyses led to similar results. In this bay, P . microps is a first‐order predator with a low degree of omnivory. Despite a preferential consumption of the amphipod C orophium arenarium , we assumed that this goby behaves as a generalist feeding on a uniform variety of endofauna taxa.

Stable isotope analyses on archived fish scales reveal the long‐term effect of nitrogen loads on carbon cycling in rivers - Jean‐Marc Roussel; Charles Perrier; Jaakko Erkinaro; Eero Niemelä; Richard A. Cunjak; Dominique Huteau; Pascal Riera (Global Change Biology, 2014)
Stable isotope analysis of organic matter in sediment records has long been used to track historical changes in productivity and carbon cycling in marine and lacustrine ecosystems. While flow dynamics preclude stratigraphic measurements of riverine sediments, such retrospective analysis is important for understanding biogeochemical cycling in running waters. Unique collections of riverine fish scales were used to analyse δ 15 N and δ 13 C variations in the food web of two European rivers that experience different degrees of anthropogenic pressure. Over the past four decades, dissolved inorganic N loading remained low and constant in the Teno River (70°N, Finland); in contrast, N loading increased fourfold in the Scorff River (47°N, France) over the same period. Archived scales of Atlantic salmon parr, a riverine life‐stage that feeds on aquatic invertebrates, revealed high δ 15 N values in the Scorff River reflecting anthropogenic N inputs to that riverine environment. A strong correlation between dissolved inorganic N loads and δ 13 C values in fish scales was observed in the Scorff River, whereas no trend was found in the Teno River. This result suggests that anthropogenic N‐nutrients enhanced atmospheric C uptake by primary producers and its transfer to fish. Our results illustrate for the first time that, as for lakes and marine ecosystems, historical changes in anthropogenic N loading can affect C cycling in riverine food webs, and confirm the long‐term interactions between N and C biogeochemical cycles in running waters.

Resource partitioning among cladocerans in a littoral macrophyte zone: implications for the transfer of essential compounds - Hélène Masclaux; Gilles Bourdier; Pascal Riera; Martin J. Kainz; Lionel Jouve; Emilie Duffaud; Alexandre Bec (Aquatic Sciences, 2014)

Food web structure within kelp holdfasts ( Laminaria ): a stable isotope study - Gauthier Schaal; Pascal Riera; Cédric Leroux (Marine Ecology, 2012)
Kelp holdfasts are highly reticulated structures which host a large diversity of small fauna. These microhabitats have been reported to play a crucial role in the biodiversity associated to kelp forest ecosystems. This study aimed at identifying trophic links and the main food sources sustaining food webs within communities associated with kelp holdfasts, through a stable isotope (δ 13 C and δ 15 N) approach. Sampling of the main invertebrates inhabiting Laminaria digitata holdfasts, and of their potential food sources, took place in February and May 2007. Stable isotope results reveal that most of the primary consumers, including filter‐feeders and deposit‐feeders, rely on the particulate organic matter sedimented within kelp holdfasts. Only three grazers departed from this general pattern. The correspondence between the stable isotope ratios of predators and sediment consumers indicated that this source is at the base of the main pathway through which energy and matter transit in the food web. δ 15 N ranges found for consumers revealed that the food web associated with kelp holdfasts is composed of 3.5 levels. In spite of the low diversity of food sources at the base of the food web, these microhabitats can therefore be considered micro‐scale ecosystems, from a functional perspective.

Food web analysis in intertidal Zostera marina and Zostera noltii communities in winter and summer - Vincent Ouisse; Pascal Riera; Aline Migné; Cédric Leroux; Dominique Davoult (Marine Biology, 2012)

Microscale variations of food web functioning within a rocky shore invertebrate community - Gauthier Schaal; Pascal Riera; Cédric Leroux (Marine Biology, 2011)

A seasonal stable isotope survey of the food web associated to a peri-urban rocky shore - Gauthier Schaal; Pascal Riera; Cédric Leroux; Jacques Grall (Marine Biology, 2010)